Decision Support Systems and Their Relationship to Information Technology Re-Engineering Academic and Administrative Systems in Palestinian Higher Education Institutions - Radwan M. Abu Mwais; Mohannad M. Abu Mwais; Samer M. Arqawi; Samy S. Abu-Naser; Mazen J. Al Shobaki (International Journal of Supply Chain Management, 2020)
Abstract: The aim of the research is to identify decision support systems and their relationship to information technology, to re-engineer academic and administrative systems in Palestinian higher education institutions. The research was applied to four Palestinian universities (Al-Aqsa University, Islamic University, Al-Azhar University, and University of Palestine), and the academic research sample with an administrative position. The descriptive analytical approach was used and secondary data was obtained through a survey list consisting of (81) items that were distributed to the research community using stratified random sample according to the university. (250) survey lists were distributed and (216) were recovered with a recovery rate of (86.4%). The study found a set of results, the most important of which are: The existence of a positive statistically significant relationship between decision support systems and information technology used in the application of re-engineering of academic and administrative systems in Palestinian higher education institutions. The results showed that there are statistically significant differences between the average answers of the respondents attributed to "university, gender, job title". The results showed that there were no statistically significant differences between the respondents ’average answers due to (age group, academic degree, and number of years of service). The research reached a set of recommendations, the most important of which are: The importance of investing more in information technology in general and decision support systems in particular, to increase the efficiency of academic and administrative processes and provide better and comprehensive services. And that Palestinian higher education institutions must reconsider their organizational structures and re-engineer their operations in line with developments in the field of information technology. And the need for Palestinian higher education institutions to develop the information technology infrastructure in general, and decision support systems in particular.